TECTONIC EVOLUTION OF MOUNT SYNIAK (THE VYHORLAT-HUTYN VOLCANIC CHAIN) IN POSTMAGMATIC STAGES: A RECONSTRUCTION BASED ON STRUCTURAL MORPHOMETRY - Andriiets, T. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Active magmatism gave rise to the Vyhorlat-Hutyn volcanic mountain chain, which had formed by the late Pliocene and is a recent indication of endogenous processes in the Ukrainian Carpathians. Mount Syniak – a stratovolcano in the NW part of the chain – has preserved its original shape, heterochronous igneous complexes and is well-marked among the landforms. However, little evidence has been collected concerning the presence of volcanic calderas, spatial and temporal distribution of neotectonic movement amplitude in the postvolcanic stages, and the tectonic activity level. These complex issues can only be clarified by analyzing a sufficient bank of geological, geophysical and geomorphological data. The goal of this research is to reconstruct the postmagmatic tectonic processes based on relief analysis. B. Filosofov's structural morphometry technique has been employed to determine the main relief indices. A complex analysis of geological, geophysical data and structural-morphometric indices yielded numerical parameters of the neotectonic vertical movements and their spatial-temporal patterns for Mount Syniak in the four posmagmatic stages. Differences in the tectonics of Grabowsk volcanic dome and the summit caldera have been determined. The summit caldera has been proved to show indications of destruction. There have been identified two local structures with high values of vertical movement amplitude: the central part of the volcano's summit caldera (m. Buz) and a section within the Grabowsk volcanic dome (between m. Berdo and h. Chervone).
Keywords: structural morphometry; neotectonic movements; GIS; relief; morphogenesis